Educational Leadership as the Primary Force in Attracting Islamic Education Customers - Zulfa, Hariratuz; Sujianto, Agus Eko; Mutohar, Prim Masrokan (Journal of Educational Research and Practice, 2024)
This study aims to discuss the role of leadership and the capabilities of a leader in implementing marketing management roles in Islamic educational institutions. The emergence of new educational institutions has created phenomena in the education sector. The forms and approaches to education are becoming more diverse and complex. Traditional entities are developing existing educational institutions, non-educational businesses, and even educational providers from abroad. Objectively, society finds it increasingly challenging to choose educational institutions. Education management becomes crucial, where the growth and development of institutions are influenced by leadership's ability to recognize the external environment to create effective strategies to compete while maintaining the essence of education itself. The research method used is library research. The research findings indicate that effective marketing strategies for Islamic educational institutions include maximizing their resources, promoting Islamic values, and utilizing information technology in marketing. Additionally, Islamic educational institutions should consider the needs and profiles of prospective students and foster good relationships with the community and local partnerships. From this research, a leader who can act as a driving force within their institution will establish a distinct identity and attract Islamic education customers to their institution. Therefore, Islamic educational institutions must continually develop appropriate and effective marketing strategies while considering market developments and student needs.